Pretreatment of palm oil mill effluent (pome) using magnetic chitosan - Saifuddin N.; Dinara S. (2023)
Chitosan is a natural organic polyelectrolyte of high molecular weight and charge density; obtained from deacetylation of chitin. This study explored the potential and effectiveness of applying chitosan-magnetite nanocomposite particles as a primary coagulant and flocculent, in comparison with chitosan for pre-treatment of palm oil mill effluent (POME). A series of batch coagulation processes with chitosan-magnetite nanocomposite particles and chitosan under different conditions, i.e. dosage and pH were conducted, in order to determine their optimum conditions. The performance was assessed in terms of turbidity, total suspended solids (TSS) and chemical oxygen demand (COD) reductions. Chitosan-magnetite particles showed better parameter reductions with much lower dosage consumption, compared to chitosan, even at the original pH of POME, i.e. 4.5. At pH 6, the optimum chitosan-magnetite dosage of 250 mg/L was able to reduce turbidity, TSS and COD levels by 98.8%, 97.6% and 62.5% respectively. At this pH, the coagulation of POME by chitosan-magnetite was brought by the combination of charge neutralization and polymer bridging mechanism. On the other hand, chitosan seems to require much higher dosage, i.e. 370 mg/L to achieve the best turbidity, TSS and COD reductions, which were 97.7%, 91.7% and 42.70%, respectively. The synergistic effect of cationic character of both the chitosan amino group and the magnetite ion in the pre-treatment process for POME brings about enhanced performance for effective agglomeration, adsorption and coagulation.